Analisis Literatur Digital Untuk Filsafat Empiris Sains: Pendekatan Terkini - Inayah, Iin; Saefurohman, Asep (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Philosophy of science is a branch of philosophy that is related to other sciences and is part of science. Philosophy defines the existence of science and uses knowledge as a way of thinking and a way of communicating science. Science can be likened to an attempt to bridge the gap between philosophy and science, so that science does not underestimate philosophy and philosophy does not view science as having a deep meaning. The Relationship between Religion and Science from the History of Islamic and Western Philosophy. Science comes from human thought, religion comes from revelation. Philosophy approaches the truth through empirical investigation, while philosophy seeks the truth through investigation, experience, and research.